Primal Screams: The Infantile Cry in Simone Weil - Darzi, Elinore (Labyrinth, 2024)
The main thesis of this essay is that non-linguistic infantile cries towards the nondefinable constitute, for Simone Weil, the essence of the human. The author begins by surveying, for the first time, Weil’s depiction of the infant’s cry as a scream of an infinite desire towards nothing definite. In the second part, in which the author analyzes the infantile cry introduced in Weil’s later writings this desire, it will be presented as fundamental to being. The infantile cry expresses mutely a desire for the indescribable good. Since it is cried from birth till death, its designation as infantile is revealed to indicate not one’s age but one’s nonlinguistic essence. While recent scholarship emphasized the importance of silence in Weil’s thought, no attention had been given to the significance of the ineffable to her philosophy. By studying the infant and infantile cry, this essay will show how the inarticulate desire towards the unattainable comprises the truth of being.